(untitled) (NTU journal for Administrative and Human Sciences (JAHS), 2023)
This Research Aims to Explain The jurisprudential ruling on animal maintenance and its impact on Islamic jurisprudence and follow the importance of research by highlighting the legal rooting, Islam looks at the animal world in general with great interest due to its importance in life and its cooperation in the benefit of man, standing on important chapters from the chapters of jurisprudence, which are the chapters related to the human relationship with animals from the expense and treatment, and the statement of the prohibition and criminalization of Islam to attack and harm animals, and it included a number of conclusions that I was able to reach after studying the subject and knowing it in all its aspects - within the limits of the Researcher’s knowledge and the breadth of the papers of the Research raised.